TUC Demonstration, March 1980 (1980)
1980 1960-2000 "TUC Demonstration, March 1980" [T0607.jpg], 1980 As part of its Campaign for Economic and Social Advance, the TUC organised a National Demonstration in London from Hyde Park to Trafalgar Square on 9 March 1980, followed by a Day of Action on 14 May, to show the strength of opposition to the Conservative Government's economic and social policies and also to the Employment Bill. On TUC platform in this photograph are [l-r] Moss Evans, Tom Jackson, David Basnett, Ken Baker, Bill Sirs [at microphone], Noel Hayes [TUC staff], Len Murray [TUC General Secretary], Roy Buckton, Clive Jenkins, Ken Graham [TUC staff]